On the Cahn-Hilliard-Oono-Navier-Stokes equations with singular potentials. Issue 12 (1st December 2016) - Miranville, Alain; Temam, Roger
Abstract : Our aim in this article is to prove the existence of solutions for a Cahn–Hilliard–Navier–Stokes system based on the Oono model and with singular potentials (and, in particular, the thermodynamically relevant logarithmic potentials). The Oono model was proposed in order to account for long-ranged (nonlocal) interactions, but also to simplify numerical simulations.